Remus: A Web Application for Prioritization of Regulatory Regions and Variants in Monogenic Diseases - Sztromwasser, Paweł; Skrzypczak, Damian; Michalak, Arkadiusz; Fendler, Wojciech (Frontiers in Genetics, 2021)
Analysis of variants in distant regulatory elements could improve current 25-50% yield of genetic testing for monogenic diseases. However, the vast size of the regulome, great number of variants, and difficulty in predicting their phenotypic impact make searching pathogenic variants in the regulatory genome challenging. New tools for identification of regulatory variants based on their relevance to the phenotype are needed. We used tissue-specific regulatory loci mapped by ENCODE and FANTOM5, together with miRNA – gene interactions from miRTarBase and miRWalk, to develop Remus – a Web application for identification of tissue-specific regulatory regions. Remus searches regulatory features linked to the known disease-associated genes, and filters them using activity status in the target tissues relevant for the studied disorder. For user convenience, Remus provides a Web interface and facilitates in-browser filtering of variant files suitable for sensitive patient data. To evaluate our approach, we used a set of 146 regulatory mutations reported causative for 68 distinct monogenic disorders, and a manually curated list of tissues affected by these disorders. In 89.7% of cases Remus identified the regulator containing the pathogenic mutation. The tissue-specific search limited the number of considered variants by 82.5%, as compared to a tissue-agnostic search. Remus facilitates identification of regulatory regions potentially associated with a monogenic disease, and can supplement classical analysis of coding variation with the aim of improving diagnostic yield in whole-genome sequencing experiments.